Considerations for Testing of COVID-19 in Travellers under Quarantine- A Retrospective Study from Palakkad District, Kerala, South India - C Sreedevi; N Divyamol; Shilu Mariam Zachariah; MG Deepak (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Until sufficient herd immunity is generated in the population, contact tracing, testing, and quarantining should be continued as key interventions in breaking the chain of transmission of Coronavirus Disease 2019 (COVID-19). Aim: To identify appropriate strategies for testing of the travellers, who were coming from high-risk areas by analysing patterns of testing among COVID-19 positive returnees. Materials and Methods: A retrospective cohort study was conducted in Community Medicine Department, Government Medical College, Palakkad, Kerala, India, during 25th September 2020 to 15th October 2020, using the secondary data available from the database of COVID-19 Contact Tracing Cell (CCTC) to determine the testing pattern among the laboratory confirmed cases of COVID-19 positive returnees in Palakkad district. Only COVID-19 positive travellers returning to Palakkad district in May 2020 were included in the study, thus the sample size obtained was 122. Data regarding age, gender, co-morbidity, presence of symptom and time of its onset, time of swab collection and reporting of results which were collected by CCTC were analysed. The Statistical Package for the Social Sciences (SPSS) version 20.0 was used to analyse the data collected by CCTC. Quantitative variables were summarised as means with standard deviations and median with interquartile ranges. Qualitative variables were summarised as percentages. Results: Between arrival and swab collection there was mean duration of 6.9±3.8 days and a median duration of seven days among the total positive returnees. Among the asymptomatic cases, the mean duration was found to be 7.4±3.6 days for the same. Between day 10 and day 12 of quarantine, 79%-91% of the cases have given swabs for Reverse Transcription Polymerase Chain Reaction (RT-PCR) testing. This had yielded 90% positive reporting within 14 days of quarantining. Total 10 cases were diagnosed after 14 days of quarantine due to late swab collection while in quarantine. Mean duration between symptom onset and swab collection among 22 symptomatic cases was 1.9±1.6 days (median=2 days). Conclusion: Testing of asymptomatic returnees from high risk area may be initiated (swab collection) by day 10 as swabs collected around 10th day of quarantine capture maximum number of positive cases. A delayed initiation for testing may prolong the time taken for diagnosis. Those who have tested negative during 14 days of quarantine should self-monitor for symptoms and reduce contact with high risk persons for one more week.